Mekanisme Penyelesaian Sengketa Terkait Klausul Keadaan Kahar dalam Kontrak Konstruksi: Studi Kasus Pengadaan Jasa di BUMN - Triwijaya, Helmy Yulian; Sami’an, S.; Hardjomuljadi, Sarwono (SIGn Jurnal Hukum, 2024)
The COVID-19 pandemic caused significant disruptions in the execution of construction contracts, leading to disputes related to force majeure claims. This article examines the force majeure dispute resolution mechanism in construction contracts at XYZ Ltd, an Indonesian SOE. This research employs normative and empirical legal approaches, with a case study on XYZ Ltd. Primary data were obtained through analysis of construction contract documents, a legal opinion from the State’s Attorney, and other relevant documents. Secondary data includes statutory regulations, court decisions, and related legal literature. The data were analyzed using qualitative content analysis and case analysis techniques. The research findings reveal that XYZ Ltd resolved disputes with service providers through negotiation, taking into account the legal opinion from the State’s Attorney, which recognized the pandemic as force majeure but emphasized the principles of pacta sunt servanda and good faith. The involvement of the BPKP through a claim audit strengthened accountability and good corporate governance. The audit results served as the basis for negotiations to minimize state financial losses. This research highlights the complexity of applying force majeure clauses in construction contracts, the importance of renegotiation, and the crucial role of legal opinions and independent audits in dispute resolution at SOEs.